(untitled) (Revista Contexto & Saúde, 2023)
Objective: a pilot study aimed at monitoring admissions in the emergency department (ED) of a University Hospital utilizing the Information System and Monitoring of Emergency Department Admissions (Simips). The Simips system was designed to track ED admissions, generate information, and provide valuable insights to enhance clinical practice, bed management, care quality, and patient safety risk assessment. Method: this study was a pilot investigation that monitored admissions of adult patients in the Emergency Department (ED) from admission for inpatient care until discharge, using the Simips system. The sample consisted of medical records of adult patients admitted for inpatient care in the ED during the period from June to August 2019. Socio-epidemiological data, severity scores, nursing care dependency scores, National Early Warning Score (News), occurrence of adverse events, length of stay, and discharge outcomes were collected. Results: 158 medical records were analyzed, with a median age of 65 years. In terms of nursing care dependency, 89% were classified as requiring minimal care on the first day of hospital admission. The frequency of adverse events was 39.2%, with medication administration delay (12%) and lack of medication reconciliation (8.9%) being the most prevalent. Conclusion: the study revealed a prolonged length of stay for patients admitted for inpatient care in the emergency department, with a predominant presence of elderly patients and a high incidence of adverse events.